2011
DOI: 10.4236/ce.2011.24059
|View full text |Cite
|
Sign up to set email alerts
|

Meeting Their Fullest Potential: The Beliefs and Teaching of a Culturally Relevant Science Teacher

Abstract: As elementary and middle school children of color continue to score poorly on science standardized tests, culturally relevant teaching has been shown to be an effective approach to addressing the social and academic needs of students from diverse backgrounds. In this article, we illustrate how the theory of culturally relevant pedagogy is embraced in the teaching beliefs of a sixth grade science teacher in a rural, low socioeconomic, predominantly African American school. The findings from a qualitative case s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 24 publications
(31 reference statements)
0
28
0
3
Order By: Relevance
“…Classroom Relationships should be equitable and productive in all science classrooms, not just those that exemplify cultural relevance. What made these particular relationships reflective of CRP, however, was that there were often group and individual goals for success that promoted a collectivist, “family‐like” environment (e.g., Mensah, ; Patchen & Cox‐Petersen, ), patterns of interaction demonstrated by the teacher that were determined to be culturally congruent with students’ and families’ linguistic and cultural backgrounds (e.g., Chigeza, ; O. Lee, ), and student groups that purposefully supported one another's learning in ways that assured success for all (e.g., Kelly‐Jackson & Jackson, ). As a result, culturally responsive classroom relationships were often noted alongside inquiry‐based practices such as Obtaining, Evaluating, and Communicating Information as referred to in this passage reported by Carlone et al () in their ethnographic study:
In countless ways, Ms. Wolfe held students accountable for critically listening to and jointly constructing knowledge with their partners in small groups and whole groups.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Classroom Relationships should be equitable and productive in all science classrooms, not just those that exemplify cultural relevance. What made these particular relationships reflective of CRP, however, was that there were often group and individual goals for success that promoted a collectivist, “family‐like” environment (e.g., Mensah, ; Patchen & Cox‐Petersen, ), patterns of interaction demonstrated by the teacher that were determined to be culturally congruent with students’ and families’ linguistic and cultural backgrounds (e.g., Chigeza, ; O. Lee, ), and student groups that purposefully supported one another's learning in ways that assured success for all (e.g., Kelly‐Jackson & Jackson, ). As a result, culturally responsive classroom relationships were often noted alongside inquiry‐based practices such as Obtaining, Evaluating, and Communicating Information as referred to in this passage reported by Carlone et al () in their ethnographic study:
In countless ways, Ms. Wolfe held students accountable for critically listening to and jointly constructing knowledge with their partners in small groups and whole groups.
…”
Section: Resultsmentioning
confidence: 99%
“…When present, this practice coincided with explicit CRP practices (7% of all coded excerpts, present with CRIOP pillars 62 times) most often around Discourse , Classroom Relationships , and Curriculum (refer to Figure ). In addition, the inquiry‐based practices Analyzing and Interpreting Data (e.g., O. Lee, ; Lim & Calabrese Barton, ), Constructing Explanations and Designing Solutions (e.g., Kelly‐Jackson & Jackson, ), and Obtaining, Evaluating, and Communicating Information (e.g., Nashon & Anderson, ) were exclusively linked with this practice. Meaning that, when present in culturally responsive science education studies, Engaging in Argument from Evidence was observed with only these other science and engineering practices.…”
Section: Resultsmentioning
confidence: 99%
“…By demanding a higher level of academic success for the entire class, individual success did not suffer” (p. 480). By fostering community building in the classroom (Kelly‐Jackson & Jackson, ), teachers attempted to create respectful and inclusive science learning environments where multiple perspectives were acknowledged (Johnson, ).…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with Gay's () initial emphasis on curriculum, research on culturally responsive science education has primarily focused on the inclusion of indigenous‐ and culturally specific knowledge in the official curriculum (e.g., Lewthwaite & McMillan, ) but has also been used to examine professional development programs (e.g., Roehrig, Dubosarsky, Mason, Carlson, & Murphy, ). Consistent with Ladson‐Billings’ (, ) original focus, much of the work to date on culturally relevant teaching practices has centered on pre‐ and in‐service science teachers’ beliefs about the importance of attending to culture in the science classroom (Atwater, Freeman, Butler, & Draper‐Morris, ), practices in the science classroom (Kelly‐Jackson & Jackson, ), and supports provided when designing culturally relevant lessons (Mensah, ). However, pockets of research have examined critical consciousness‐ and cultural competence building in students (Tsurusaki et al., ) and the degree to which indigenous students’ experiences are included in the classroom (Nam et al., ).…”
Section: Theoretical Backgroundmentioning
confidence: 97%
“…Still missing are clear pedagogical examples that make real on science for all claims (Gutiérrez & Barton, ; Johnson, ; Varelas et al, ). For researchers, such examples offer an opportunity to study how science teachers implement CRP in their classrooms and to identify effective strategies for utilizing CRP in science (Kelly‐Jackson & Jackson, ; Mensah, ; Parsons & Carlone, ). Without question, this study requires an understanding of schools as complex, culturally dynamic and fluid sites (Nasir & Hand, ) wherein teachers are cultural and political workers whose CRP mindsets often get “negotiated in the context of social interactions” (Ye, Varelas, & Guajardo, , p. 873).…”
Section: Literature Reviewmentioning
confidence: 99%